PENDAMPINGAN TATA LAKSANA PENGGUNAAN MORINGA OLEIFERA LAM SEBAGAI ANTIOKSIDAN PAPARAN BENZO(A)PYRENE PADA IBU PRAKONSEPSI - Rila Rindi Antina; Selvia Nurul Qomari (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2020)
The progesterone hormone stimulates uNK (Uterine Narural Killer) cells to produce immunomodulatory proteins or changes the cytokine environment, then changes the function of uNK cells. This process occurs through progesterone activity on the differentiation of T cells into Th1 and Th2 (Piccinni et al, 2015). In this study, the mother was carried out a laboratory examination to check the level of exposure to benzopyrents using IV blood samples, the results of the laboratory tests were then used as the basis for the implementation of assistance, previously counseling was carried out to preconception mothers regarding the procedures for using moringa oleifera, preconception mothers assistance was carried out every week for 3 months, after several months of mentoring, it was found that some of the women had succeeded in getting pregnant with a positive PP test result and the ultrasound results contained a pregnancy bag. In May-June 2019, Anna Medika Hospital Madura served 30 preconception mothers with a history of blighted ovum / abortion. During the activity, the mother was very enthusiastic about the material presented. So that mothers and families can follow the material suggestions that have been delivered and assistance is found that some women have succeeded in getting pregnant with positive PP test results and ultrasound results there are pregnancy bags.